2021
DOI: 10.3390/su132313430
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Use of Machine Translation: Usability and Perceived Quality from the End-User Perspective

Abstract: Artificial intelligence-grounded machine translation has fundamentally changed public awareness and attitudes towards multilingual communication. In some language pairs, the accuracy, quality and efficiency of machine-translated texts of certain types can be quite high. Hence, the end-user acceptability and reliance on machine-translated content could be justified. However, machine translation in small and/or low-resource languages might yield significantly lower quality, which in turn may lead to potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
(35 reference statements)
2
13
0
Order By: Relevance
“…With the rapid development of artificial intelligence, machine translation (MT) has gained popularity in recent years. MT tools are widely used among individuals, from pupils [1] to senior citizens [2]. In everyday life, this technology can be used for household tasks, news, personal communication, internet shopping, entertainment, and legal services [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of artificial intelligence, machine translation (MT) has gained popularity in recent years. MT tools are widely used among individuals, from pupils [1] to senior citizens [2]. In everyday life, this technology can be used for household tasks, news, personal communication, internet shopping, entertainment, and legal services [2].…”
Section: Introductionmentioning
confidence: 99%
“…MT tools are widely used among individuals, from pupils [1] to senior citizens [2]. In everyday life, this technology can be used for household tasks, news, personal communication, internet shopping, entertainment, and legal services [2]. Most importantly, the 21st century has witnessed much integration of MT into education, especially in language learning.…”
Section: Introductionmentioning
confidence: 99%
“…Good results can be achieved by creating a contextual curriculum and lesson plans, using a variety of innovative and attractive activities according to the interests of the OSH experts, and discussing topics that are close to their professional environment ( 24 , 25 ). Thirdly, the general digital skills of OSH experts should be improved through training that includes the use of different machine translation services and language technologies which are becoming common in everyday practice for a variety of reasons and purposes ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rapid advances in MT technology, in some languages, especially low-resource languages, the quality of MT can be poor because of low amounts of parallel data [22,23]. Recent research has found that public perceptions of the potential and quality of MT are inadequate [24,25]. Nevertheless, members of the public, possibly including children, often use MT and consider its quality to be acceptable and equivalent to human translation [26].…”
Section: Literature Overviewmentioning
confidence: 99%